REDESAIN RANCANGAN UNDANG UNDANG OMNIBUS LAW CIPTA LAPANGAN KERJA - Basuki Kurniawan (JURNAL AKTA YUDISIA, 2021)
The investment climate is difficult to develop when there are too many overlapping regulations from the center to the regions, and the old licensing procedure is a source of ongoing problems. Seeing this, President Jokowi made a breakthrough by using the Omnibus Law for Job Creation or often referred to as the Cilaka Omnibus Law Bill. This is something new in Indonesia, but it is a breakthrough in resolving legal chaos in Indonesia. However, the desire of the Government to get a response from a fairly large wave of demonstrations from the workers and society. The demonstration was based on the contents of the articles in the Job Creation Omnibus Law Bill which were deemed to be detrimental to the Indonesian people and workers. Based on the author's opinion, we conclude several things. First, the Job Creation Omnibus Law Bill has several deeper corrections, especially in the paradigm and substance of regulations regarding layoffs, permits, and regional autonomy (decentralization). Second, the Cilaka Omnibus Law Bill intends to reduce the existence of hyper-regulation (the number of laws and regulations), but the bill creates derivative regulations that make more and more new rules emerge. So it is best if the Omnibus Law Job Creation Bill needs to be rearranged while still involving the wider community in providing input and views for the perfection of this Job Creation Bill. Keywords: Omnibus Law, Job Creation